(3OdGdI GdHQgGf Ydi Cf aj GdEecGf CHOY eeG cGfs - (3GdHbGYj , EHQGgje Hf YeQ Hf MSf GdQHGW Hf Ydj Hf CHj HcQ GdHbGYj GdTGaYj, HQgGf GdOjf CHh GdMSf,J (B885 (3g` s
(3ChdgG (B:s
(3hHYO CjgG GdNdGf cJGH SCdfi ajg HYV GdENhGf dCeQ GbJVGg hGddg GdeSJYGf SejJg OdGdI GdHQgGf Ydi Cf ai GdEecGe CHOY eeG cGf s
(3BNQgG (B:s
(3eeG HfJ GdadGSaI YbOgG Ydjg Ch eG PgHJ Edjg GdeYJRdI hGdMeO ddg QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B56 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B71s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3Yde GdcdGe (B- (3JjehQ (B180) s
Keywords: (3GdJhMjO hGdedd hGdfMds